1997
DOI: 10.1021/la960673o
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Adsorption and Oxidation on Cu/Mg/Al Mixed Oxide Catalysts Prepared via Hydrotalcite-Type Precursors

Abstract: Cu/Mg/Al catalysts obtained by controlled calcination of hydrotalcite-type (HT) anionic clays may be new interesting and cheap catalysts for the selective catalytic reduction (SCR) of NO by NH3. In this paper the ammonia adsorption and oxidation on Cu x Mg0.710 - x Al0.290 catalysts (x = 0.022, 0.046, and 0.072, as atomic ratio), obtained by calcination for 14 h at 923 K of HT precipitates, have been investigated and compared with those of the corresponding Mg0.710Al0.290 sample. The presence of copper strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 39 publications
6
26
0
Order By: Relevance
“…Zawadzki [1] also suggested that -NH would react with molecular O 2 to produce NO at higher temperatures, but the author did not propose the in situ reaction between the NO and -NH x . Since the key intermediate (NO x ) of the SCR routes proposed by Ramis et al [8,14,[35][36][37][38] was detected in our experiment (Figs. 6 and 7), and the NH 3 could rapidly react with the in situ-formed NO x ad-species (Fig.…”
Section: Nh 3 Adsorptionsupporting
confidence: 52%
“…Zawadzki [1] also suggested that -NH would react with molecular O 2 to produce NO at higher temperatures, but the author did not propose the in situ reaction between the NO and -NH x . Since the key intermediate (NO x ) of the SCR routes proposed by Ramis et al [8,14,[35][36][37][38] was detected in our experiment (Figs. 6 and 7), and the NH 3 could rapidly react with the in situ-formed NO x ad-species (Fig.…”
Section: Nh 3 Adsorptionsupporting
confidence: 52%
“…Cu-Mg-Al hydrotalcite-like materials were used as catalysts for Bayer-Villiger oxidation of ketones [14]. Their calcined forms were used in the oxidative coupling of phenylethyne [15], adsorption and oxidation of ammonia [16], N 2 O decomposition [17] as well as in decomposition and reduction of nitrogen oxides and sulphur oxides [e.g. 6,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that noble metals such as Pt, Ir and Au were active for the reaction of SCO of NH 3 at low temperature, however, the selectivity of N 2 was not satisfied for the reason that the main by-product at low temperature was N 2 O [4][5][6][7][8] [9][10][11][12][13][14][15][16][17], and many ion-exchanged zeolite catalysts [18][19][20][21][22], have also been investigated for the SCO of NH 3 , but NH 3 conversion levels of these catalysts at low temperature were not high enough to be of practical use.…”
Section: Introductionmentioning
confidence: 99%